Advances in Multiple Criteria Decision Making and Human Systems Management : Knowledge and Wisdom. - Shi, Yong, 1956-; Olson, David L., 1944-; Stam, Antonie (IOS Press, 2007)
This volume, edited as a Festschrift in honor of Prof. Milan Zeleny, reflects and emulates his unmistakable legacy: the essential multidimensionality of human and social affairs. There are many levels of this multidimensionality presented in this volume: 1. Multidisciplinarity of contributed papers 2. Multinationality of their authors, extending even to the editors and the publisher and 3. Multicultural and multilevel exposition, ranging from empirical studies to philosophical foundations. Generally, thes papers can be divided into three parts: Multiple Criteria Decision Making; Social and Human System Management; and Information, Knowledge and Wisdom Management. It is the recognition of multidimensionality in decision making, economics, optimization, sysems, cybernetics and the pursuit of knowledge that bear the stamp of specific Zeleny's contributions. His life-long dedication to multidimensionality has produced an ultimate multidimensional being, living in academic 'multiverse', functioning in a boundayless world of all continents, cultures and countries. This book is as diverse and as multidimensional as the man and his work.